Effects of Low-Carbohydrate Diet and Exercise Training on Gut Microbiota - Sun, Shengyan; Lei, On Kei; Nie, Jinlei; Shi, Qingde; Xu, Yuming; Kong, Zhaowei (Frontiers in Nutrition, 2022)
Objective This study was aimed to evaluate the effects of low-carbohydrate diet (LC) and incorporated high-intensity interval training (HIIT) or moderate-intensity continuous training (MICT) on gut microbiota, and the associations between changes in gut microbiota and cardiometabolic health-related profiles. Methods Fifty overweight/obese Chinese females (age 22.2 ± 3.3 years, body mass index 25.1 ± 3.1 kg/m–2) were randomized to the groups of LC, LC and HIIT (LC-HIIT, 10 repetitions of 6-s sprints and 9-s rest), and LC and MICT group (LC-MICT, cycling at 50–60% V̇O2peak for 30 min). The LC-HIIT and LC-MICT experienced 20 training sessions over 4 weeks. Results The 4-week LC intervention with/without additional training failed to change the Shannon, Chao 1, and Simpson indexes (p > 0.05), LC increased Phascolarctobacterium genus, and LC-HIIT reduced Bifidobacterium genus after intervention (p < 0.05). Groups with extra exercise training increased short-chain fatty acid-producing Blautia genus (p < 0.05) and reduced type 2 diabetes-related genus Alistipes (p < 0.05) compared to LC. Sutterella (r = −0.335) and Enterobacter (r = 0.334) were associated with changes in body composition (p < 0.05). Changes in Ruminococcus, Eubacterium, and Roseburia genera were positively associated with blood pressure (BP) changes (r = 0.392–0.445, p < 0.05), whereas the changes in Bacteroides, Faecalibacterium, and Parabacteroides genera were negatively associated with BP changes (r = −0.567 to −0.362, p < 0.05). Conclusion LC intervention did not change the α-diversity and overall structure of gut microbiota. Combining LC with exercise training may have additional benefits on gut physiology. Specific microbial genera were associated with LC- and exercise-induced regulation of cardiometabolic health.